Making Evidence Work for Communities: The Role of Nongovernmental Organizations in Translating Science to Programs. - Drake JK; Hutchings JE; Elias CJ (Journal of Women's Health (15409996), 2010)
Evidence-informed public health refers to the process of applying proven interventions within the context of community preferences in order to achieve positive health impacts. A key role for nongovernmental organizations (NGOs) in evidence-informed public health is to use and expand on research to help shape appropriate interventions for diverse communities. This article suggests that NGOs are particularly well positioned for this role for a number of reasons, including their geographic reach, their engagement with diverse stakeholders, and their extragovernmental position, which enables them to develop and advocate for innovative, scientifically sound solutions to long-standing health challenges. Three case studies are presented that highlight how NGOs can harness these advantages to shape evidence-informed policies and programs to improve women's health: PATH's multicountry HPV Vaccines project, the International Consortium for Emergency Contraception, and a collaborative effort to combat maternal mortality in Mali.